Cereal self-sufficiency in Arab Countries: Evidence from a dynamic difference GMM approach within a food systems framework - KERRAR, Mohammed Abdelghani; NEDJAR, Malika (The International tax journal, 2026)
Food security remains a major challenge in Arab countries due to high cereal import dependence, demographic pressures, and exposure to external shocks. This study examines the determinants of cereal self-sufficiency in 17 Arab countries over the period 2010–2024 using a Difference GMM approach within a Food Systems Framework. The results reveal significant persistence in cereal self-sufficiency, indicating that past performance strongly influences current outcomes. Rural population share exerts a positive and statistically significant effect, whereas political stability is negatively associated with cereal self-sufficiency, reflecting contrasting food-security strategies across Arab economies. By contrast, population growth, water stress, GDP per capita growth, food price inflation, and cereal yields do not exhibit statistically significant effects. The findings suggest that cereal self-sufficiency is driven primarily by demographic and institutional factors rather than conventional production and macroeconomic variables. The study highlights the need for integrated policies combining rural development, effective governance, and long-term food-system resilience.